Efficiency and Labour Absorption in Irrigated Rice Farms in Nueva Ecija: Philippines - M. Galang, Luzviminda (1990)
The focus of the study is on the determination of economic efficiency and labour absorption capacity of rice farms operating under the two types of small-scale irrigation systems (gravity type and pump type) in Nueva Ecija , Philippines. Rice farms from both types of irrigation systems were assessed using the normalized restricted profit function . Data from two hundred and sixty two rice farmers, 110 from Cristamakita Farmer Irrigators' Association (CFIA) comprising the gravity irrigated farms and 122 from Penaranda Irrigators' Association (PIA) comprising the pump irrigated rice farms , was analysed using the SAS Syslin computer package. Profitability analysis shows that among the variable inputs considered, only labour, fertilizer and seeds possess the correct a priori signs and only fertilizer is significant to farm profit. Land has positive coefficient as expected but the coefficient is not significant. Land tenure status of the farmers affects farm profit in favour of owner-operators. Owner-operators have greater income per farm and per hectare compared to other farmer-groups considered, regardless of farm proximity to the irrigation canal. Empirical findings show no difference in relative economic efficiency between the farmer-groups considered. Both farmer groups operate on the same level of economic efficiency. Both farmer-groups failed to maximize prof it in the short run . Both groups of farmers were not successful in equating the marginal value products of the variable resources to their respective prices. The elasticity of demand for labour with respect to its price is inelastic (-0.29). This implies that under existing farm conditions, rice farming is unlikely to absorb excess farm labour without decreasing wage rate. Labour however, is responsive to output price changes. Fertilizer was found out to be responsive to its own price (-1.43) and also responsive to output price. Response of paddy supply to changes in the price of the variable inputs supports a priori expectations, but all the coefficients are not significant. Moreover, paddy supply is more sensitive to seed price compared to the price of labour, fertilizer, pesticides and animal-machine. Human labour and animal-machine were found to be complementary inputs. The rest of the inputs considered were also found to be complementary with each other like labour with fertilizer, labour with seeds and labour with pesticides. This shows that decrease in the prices of fertilizer, pesticides and seeds will encourage increase in their usage hence, will also increase labour demand Demand for variable input s was not responsive to land, but responsive to irrigation fee. The results of the study indicate room for increasing food supply through improvement of farmers' allocative efficiency.